Evaluation of Body Weight, Serum Glucose Level, and Oxidative Stress Parameters of Streptozotocin-Induced Diabetic Rats Administered Insulin and Alkaloid Leaf Extract of Jatropha tanjorensis - Umoh, Idongesit Bassey; Ukoh, Imoh Emmanuel (African Journal of Medicine, Surgery and Public Health Research, 2025)
This study investigates the therapeutic potential of alkaloid leaf extract of Jatropha tanjorensis (ALEJT) in managing diabetes mellitus (DM), particularly its effects on body weight, serum glucose, and oxidative stress parameters, in comparison to insulin. DM is associated with weight loss and elevated oxidative stress, prompting the need for alternative therapies. Forty female albino rats (150–200 g) were divided into four groups (n = 6). Group 1 served as the normal control, while diabetes was induced in Groups 2–4 via a single intraperitoneal injection of streptozotocin (STZ, 80 mg/kg). Rats with fasting blood glucose ≥ 200 mg/dL after 72 hours were considered diabetic. Group 2 served as the diabetic control; Group 3 received ALEJT (500 mg/kg orally), and Group 4 received insulin (2 IU/kg/day i.p) for 21 days. Body weight and serum glucose were monitored, and serum antioxidant markers—glutathione (GSH), superoxide dismutase (SOD), glutathione peroxidase (GPx), catalase (CAT), total antioxidant capacity (TAC), and malondialdehyde (MDA) were evaluated using standard methods. Results showed no significant weight gain in diabetic rats treated with ALEJT, while all diabetic groups had reduced percentage growth rates. Serum glucose levels were significantly elevated in diabetic rats (p < 0.001). Diabetic controls showed a marked decrease in GSH, SOD, GPx, and TAC, with a corresponding increase in MDA (p < 0.001). Treatment with ALEJT or insulin improved oxidative stress parameters, with ALEJT demonstrating superior efficacy in restoring GSH and GPx levels (p < 0.001) compared to insulin. The findings suggest that ALEJT offers protective effects against oxidative stress and may serve as a natural, safe alternative in DM management, with greater antioxidant benefits than insulin.